Acoustic intensity imaging methods for in-situ wave propagation - WEYNA, Stefan (Archives of Acoustics, 2010)
In the paper the author has described the visualization methods in acoustic flow fields and show how these methods may assist scientists to gain understanding of complex acoustic energy flow in real-life field. A graphical method will be presented to determine the real acoustic wave distribution in the flow field. Visualization of research results, which is unavailable by conventional acoustics metrology, may be shown in the form of intensity streamlines in space, as a shape of floating acoustic wave and intensity isosurface in three-dimensional space. In traditional acoustic metrology, the analysis of acoustic fields concerns only the distribution of pressure levels (scalar variable), however in a real acoustic field both the scalar (acoustic pressure) and vector (the acoustic particle velocity) effects are closely related. Only when the acoustic field is described by both the potential and kinetic energies, we may understand the mechanisms of propagation, diffraction and scattering of acoustic waves on obstacles, as a form of energy image. This attribute of intensity method can also validate the results of CFD/CAA numerical modeling which is very important in any industry acoustic investigations.